(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Sports participation has been adjudged to enhance healthy living. This study described anthropometric and physiological (A-P) profiles of university athletes based on types of sports (ToS) and duration (in years) of participation (DoP). One hundred and twenty-nine athletes (69 males, 60 females), aged l5-36, who had played averagely for 5.78±0.29years, from nine games and preparing for Ghana University Sports Association (GUSA) 2014 participated in the study. Ex-post facto research design was adopted. Data on ToS, DoP, age, height, weight, body mass index, waist and hip circumference, body fat and water, blood pressure and heart rate were collected, entered into SPSS Data Editor 17.0 and exported to STATA 11 where multiple regression analysis and t-test were carried out. ToS has significant effects on anthropometric [F(7,121) = 2.478, p<0.05] and physiological [F(5,123) = 5.532, p<0.05] profiles. DoP has significant effects on physiological profiles [F(7,121) = 5.185, p<0.05] of the athletes. Significant differences existed in age, height, weight, BMI, WHR and SBP (p<0.05) based on gender. BMI and HR values were not sufficiently healthy for athletes. Clinical intervention is imperative to determine actual cardiovascular risks of the sample because they might be unfit for national assignment if not properly monitored and trained to be consistent in moderate fitness lifestyles.